PENGARUH SISTEM REWARD, MOTIVASI EKSTRINSIK DAN LINGKUNGAN KERJA NON FISIK TERHADAP KOMITMEN KARYAWAN - Vinanti, Laura Odile; Fahrurrozi, Moh; Yuliandari, Ni Kadek (Fakultas Ekonomi, 2025)
This research aims to test and analyze the effect of the Reward System, Extrinsic Motivation, and Non-Physical Work Environment on Employee Commitment at the CU Sang Timur Consumers Cooperative in Banyuwangi. The CU Sang Timur Consumers Cooperative is a member-based financial institution focused on empowering the economic activities of its members. In addition to its Savings and Loan Unit, CU Sang Timur also operates as a Trading Unit for Agricultural Production Facilities. CU Sang Timur has been established since 2007 in Banyuwangi, specifically on Jalan Raya Grajagan, Dusun Sidoagung, Desa Karetan, Kecamatan Purwoharjo, Banyuwangi Regency. This study uses a quantitative method by distributing questionnaires, and the data analysis methods used include instrument testing, classical assumption testing, multiple linear regression analysis, hypothesis testing, and the coefficient of determination. The questionnaires were distributed to 57 employees as respondents. Data processing was carried out using SPSS v.25 for Windows. The results of the t-test hypothesis (t count > t table), with t table = 2.0057, show that the Reward System (X1) has t count = 6.573, Extrinsic Motivation (X2) has t count = 2.034, and Non-Physical WorkEnvironment (X3) has t count = 2.057. All of these factors have a significant and partial effect on Employee Commitment at CU Sang Timur Consumers Cooperative in Banyuwangi. The F-test result (F count > F table 28.526 > 2.779) indicates that, simultaneously, the Reward System, Extrinsic Motivation, and Non-Physical Work Environment significantly affect Employee Commitment at CU Sang Timur Consumers Cooperative in Banyuwangi.